Reductivism versus perspectivism versus holism: A key theme in philosophy of science, and its application to modern linguistics. - Collin, Finn; Durst‐Andersen, Per (Theoria: A Swedish Journal of Philosophy, 2024)
We use recent developments within philosophy of science and within certain strands of linguistic research to throw light on each other. According to Ronald Giere's perspectivist philosophy of science, the scientific understanding of reality must proceed along different, mutually irreducible lines of approach. Giere's proposal, however, leaves unresolved the problem of how to integrate the ever‐growing multitude of highly diverse scientific accounts of what is, after all, one and the same world. We propose a technique for the alignment of different perspectives that will permit cross‐perspectival explanation, and thus allow for a more holistic picture of reality to emerge. With respect to modern linguistics, however, Giere's perspectivism merely legalises a de facto state of affairs, as this discipline displays the peaceful coexistence of a multitude of different theoretical perspectives. Still, this makes it all the more important to show how the different aspects of language picked out by these different perspectives combine to form one single complex reality. During our investigation, a largely overlooked type of reduction within linguistics comes to light, prevalent in classical as well as current work within speech act theory and politeness theory. We suggest how a more holistic understanding of language can be attained through our technique for integrating different perspectives.